Quantitative and Comparative Assessment of Learning in a Tongue-Operated Computer Input Device—Part II: Navigation Tasks - Yousefi, Behnaz (2012)
Tongue drive system (TDS) is a novel tongue-operated assistive technology (AT) for the mobility impaired, to empower them to access computers and drive powered wheelchairs (PWC) using their free voluntary tongue motion. We have evaluated the TDS performance in five sessions over 5–8 weeks to study the learning process in different tasks of computer access and PWC navigation on nine able-bodied subjects who already had tongue piercing and used our magnetic tongue studs throughout the trial. Computer access tasks included on-screen maze navigation and issuing random commands to measure the TDS information transfer rate. PWC navigation included driving through a ~50-m obstacle course using three control strategies. Some of the qualitative aspects of using the TDS were also evaluated based on the two Likert scale questionnaires, one of which was short (eight questions) and asked at the end of each session and the other one (46 questions) at the end of the trial. Included in this study was also a task to measure the tongue fatigue as a result of using the TDS continuously for a few hours. All performance measures showed significant improvement from the first to the second session as well as further gradual improvements throughout the rest of the sessions, suggesting a rapid learning process.